GMOs, consumerism and the global politics of biotechnology : rethinking food, bodies and identities in Africa's 21st century - Mawere, Munyaradzi; Nhemachena, Artwell (Langaa RPCIG, 2017)
"Despite sustained continental and national struggles for autonomy, sovereignty and independence in postcolonial Africa, the continent is increasingly embattled by the forces of globalisation which threaten African identity that is at the core of African struggles for continental and national unity. Situating the debates in the contemporary discourses on decoloniality, global consumerism, global food apartheid and the challenges and prospects of the emergent sharing economies, this book critically examines the importation, use and implications of genetically modified organisms (GMOs) and other such non-food products on African bodies, institutions and cultures. The book poses questions about how Africa can be decolonised both politically and in terms of global food apartheid and the dehumanising importation and use of'foreign'non-food products, some of which militate against the ethos of [African] identity, Renaissance and indigeneity. On note, the book urges the African continent to ensure the safety of imports ensuing from the global flows and circulations that are mired in the resilient invisible global matrices of power"--Back cover